Seed priming with spent tea leaves (Camellia sinensis L.) promotes early growth of black cherry tomato (Solanum lycopersicum L. var. cerasiforme) seedlings under drought stress - Tho, Luong Thi Le; Ngan, Luong Thi Thu; Khang, Luu Tang Phuc (Asia-Pacific Journal of Science and Technology, 2025)
Black cherry tomato (Solanum lycopersicum L. var. cerasiforme) is an economically important crop valuable crop but is highly sensitive to drought, which hampers seed germination and early seedling growth. While spent tea leaves (STL) are known for their biological activity, their effects on tomato germination under drought stress remain unclear. This study evaluated STL extracts from black, green, and oolong cultivars as seed priming agents to enhance germination and early growth of black cherry tomato under polyethylene glycol (PEG-6000)-induced drought stress. Tomato seeds were surface-sterilized and then soaked in STL extracts at concentrations of 1%, 2%, or 4% (w/v) for 24 hours at 25oC before sowing. Increasing PEG-6000 concentrations (0%, 4%, 8%, and 12%) caused significant reductions in germination percentage, shoot length, root length, seedling vigor index and fresh biomass, with the most severe declines observed at 12% PEG-6000. Priming with STL extracts mitigated these adverse effects in a tea type- and concentration-dependent manner. Black and oolong tea extracts at 2–4% improved germination percentage, germination speed, and vigor indices, while also enhancing radicle and plumule length, shoot height, and biomass under stress. In contrast, green tea exerted weaker or inhibitory effects. These findings suggest that black tea extract at 4% offers an effective and low-cost strategy approach to improve drought tolerance in black cherry tomato, promoting sustainable agricultural practices in the face of environmental stress.